2018
DOI: 10.1099/mgen.0.000223
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal copy number variation analysis by next generation sequencing confirms ploidy stability in Trypanosoma brucei subspecies

Abstract: Although aneuploidy usually results in severe abnormalities in multicellular eukaryotes, recent data suggest that it could be beneficial for unicellular eukaryotes, such as yeast and trypanosomatid parasites, providing increased survival under stressful conditions. Among characterized trypanosomatids, Trypanosoma cruzi, Trypanosoma brucei and species from the genus Leishmania stand out due to their importance in public health, infecting around 20 million people worldwide. The presence of aneuploidies in T. cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
6
17
0
Order By: Relevance
“…These results are consistent with the dynamics of ploidy observed in genomes SRR10246848 and SRR10246849 analyzed by Restrepo et al [28]. The lack of genomic plasticity at the chromosomal level observed for L. panamensis has also been reported in other pathogens such as T. brucei; recently, a study has shown that none of the T. brucei subspecies present aneuploidy [62]. The low aneuploidy in these pathogens could be explained as a possible feature of adaptation of these parasites to human hosts or could be related to the loss of recombination events in this species, similar to that proposed for T. brucei [62].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are consistent with the dynamics of ploidy observed in genomes SRR10246848 and SRR10246849 analyzed by Restrepo et al [28]. The lack of genomic plasticity at the chromosomal level observed for L. panamensis has also been reported in other pathogens such as T. brucei; recently, a study has shown that none of the T. brucei subspecies present aneuploidy [62]. The low aneuploidy in these pathogens could be explained as a possible feature of adaptation of these parasites to human hosts or could be related to the loss of recombination events in this species, similar to that proposed for T. brucei [62].…”
Section: Discussionsupporting
confidence: 90%
“…The lack of genomic plasticity at the chromosomal level observed for L. panamensis has also been reported in other pathogens such as T. brucei; recently, a study has shown that none of the T. brucei subspecies present aneuploidy [62]. The low aneuploidy in these pathogens could be explained as a possible feature of adaptation of these parasites to human hosts or could be related to the loss of recombination events in this species, similar to that proposed for T. brucei [62]. This is also supported by the low number of SNPs found in the L. panamensis genomes analyzed which would explain a plausible mechanism of adaptation to human infection.…”
Section: Discussionsupporting
confidence: 52%
“…Among these families, the trans-sialidase (TS) and dispersed gene family-1 (DGF-1) genes are enriched at subtelomeric regions of chromosomes [33], though other gene arrays are found throughout the chromosomes. Intriguingly, next generation sequencing has suggested that T. cruzi, like Leishmania, displays chromosomes that deviate from diploidy [34], whereas no such aneuploidy is seen in T. brucei [35]. Whether this difference relates to T. cruzi and Leishmania each having their genome housed in large numbers (> 35) of relatively small chromosomes, whereas the T. brucei genome is found in 11 relatively large chromosomes, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These aneuploidies are related to drug resistance, gene expression regulation, or host adaptation [ 60 , 61 , 62 ]. Otherwise, in T. brucei a ploidy stability exists, including the subspecies T. b. gambiense and T. b. rhodesiense [ 63 ].…”
Section: Genetic Diversity and Genome Structure Of T Crmentioning
confidence: 99%